Effect of frailty on the risk of all-cause mortality —a 12-year follow-up study of community residents aged 45 years and above in Shanghai - SUN Shuangyuan; RUAN Ye; GUO Yanfei; WANG Chunfang; JIANG Anli; DONG Yujun; SHI Yan; WU Fan (Shanghai yufang yixue, 2022)
ObjectiveTo analyze the effect of frailty status on the risk of mortality in a community-based population aged 45 years and above in Shanghai with different characteristics， and to provide further basis for population-based interventions for frailty and prevention of adverse outcomes.MethodsData were derived from baseline data from the Shanghai prospective study on AGEing and adult health （2009-2010） and cohort follow-up of causes of death up to October 30， 2021. Frailty index （FI） scores were constructed from 40 variables. Those with frailty index FI≥0.2 were judged to be in a frail state， and a multifactorial Cox regression model was used to calculate the hazard ratio （HR） to evaluate the effect of frailty status on the risk of death in different age groups by gender. Socioeconomic characteristics （age， residence， marital status， education and family economic level， etc.） and health-related behaviors （smoking， alcohol consumption， fruit and vegetable intake， social participation， etc.） were included as control variables.ResultsThe study included 7 978 subjects， 777 （9.7%） of whom were in a frail state. After （11.3±1.8） years of follow-up， 1 043 （13.1%） individuals were dead， including 214 （27.5%） who were frail. The results of the multifactorial Cox regression analysis showed that the effect of frailty on the risk of death in each subgroup was in descending order of men in the middle-aged group （45‒ years） （HR=2.92， 95%CI： 1.38-6.19）， women in the low-aged elderly group （60‒ years） （HR=1.68， 95% CI： 1.08-2.60）， and women in the old-aged elderly group （≥75 years and older） （HR=1.59， 95%CI： 1.22‒2.06）.ConclusionFrailty is associated with the risk of death， and we should focus on the frailty status of men aged 45~59 years and women aged 60 years and above. Early screening and assessment of frailty status and taking appropriate preventive interventions may reduce the occurrence of adverse outcomes and premature death.